Kepastian Hukum Perjanjian Kredit Tanpa Disertai Perjanjian Jaminan - Amadis, Fay Alejandra; Hariyani, Iswi; Tektona, Rahmadi Indra; Manggala, Ferdiansyah Putra (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2024)
Basically, providing credit with or without collateral, a credit agreement is a principal agreement that contains about the parties, the object of the agreement between the creditor and the debtor, whose rights and obligations of the parties are even to strengthen the fulfillment of achievements, strengthened by a guarantee agreement that is useful if at the time of the debtor's default, the guarantee can be auctioned and the auction results can be used as the fulfillment of achievements. However, in the case of decision No. 21/Pdt.G.S/2019/PN Tte., even though it has met the requirements of the simple lawsuit requirements in relation to not making a guarantee agreement, there are obstacles in the execution of the object that is placed as collateral in the principal agreement. The purpose of this study is to review and find legal certainty of credit agreements without being accompanied by land guarantee agreements. Second, to examine and find the judge's ratio of the application for collateral confiscation that is not the property of the debtor. Third, to find the concept of related execution in decision No. 21/Pdt.G.S/2019/PN Tte. Ratio decidendi on the application for confiscation of collateral that does not belong to the debtor. The Judge considered that the application for bail confiscation was rejected based on the fact that the plaintiff had no intention that the defendant would move or transfer the object of the dispute and because the examination of this case was carried out based on a simple lawsuit that was limited by the time of the examination, the judge considered it quite reasonable if the petition number 4 of the lawsuit should be rejected. Regulation of the ratio decidendi of execution that supports Article 20 of the Law on the Rights of Dependents. The payment of a certain amount of money can be made by auction, the location of the real execution with the payment of a sum of money.